2018
DOI: 10.1016/j.ijdrr.2018.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting post-evacuation behaviors following an earthquake: A questionnaire-based survey

Abstract: In order to elucidate the factors that influence the post-evacuation behaviors of university members following an earthquake, this study administered a questionnaire survey to 109 faculty members, graduate students, and undergraduates at a national university in Japan, and investigated the situations in which they were likely to return to their university building. Through face-to-face interviews, the participants were asked to rate the extent to which they would return to their university building, based on 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 40 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…These two experiments, the students were able to evacuate from the room in less than one minute. The common but inappropriate behavior was the return to evacuate the personal belongings which are relevant to previous study (Koshiba and Suzuki, 2018).…”
Section: Resultsmentioning
confidence: 71%
“…These two experiments, the students were able to evacuate from the room in less than one minute. The common but inappropriate behavior was the return to evacuate the personal belongings which are relevant to previous study (Koshiba and Suzuki, 2018).…”
Section: Resultsmentioning
confidence: 71%
“…Also relevant are external drivers such as utility outages and whether neighborhoods or housing are accessible (Wright and Johnston 2010). Other considerations include age, ethnicity, cultural, socio-economic status, type of dwelling, location, and social-political standpoints, which intersect to propel human action and therefore promote or hinder preparedness, evacuation, and response (Drabek 1969;Huang et al 2016;Koshiba and Suzuki 2018;Lindell and Perry 2012;Perry 1983;Shapira, Aharonson-Daniela, and Bar-Dayana 2018;Sorensen and Mileti 1988;Thompson et al 2017;Wood et al 2017;Wright and Johnston 2010).…”
Section: Evacuation Researchmentioning
confidence: 99%
“…The study emphasized the importance of collaboration between schools and the community in building a comprehensive disaster management framework. Moreover, [11] identified the factors influencing post-evacuation behavior among academic communities. Another study also showed that campuses have become important to the studies related to emergency evacuation planning during earthquakes due to their strategic location in densely populated urban areas [12].…”
Section: Introductionmentioning
confidence: 99%